Perancangan Sistem Deteksi Koefisien Kopling Magnetik pada Wireless Power Transfer menggunakan Perbandingan Respon Frekuensi dengan Metrik Euclidean Distance - Inayah Wulandari; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Wireless Power Transfer (WPT) is a wireless electrical power delivery technology consisting of two circuits, namely the sender and receiver circuits. One of the methods of sending power on WPT is to utilize magnetic induction. This method utilizes a magnetic field or inductance created between coils between two coil windings. In this type of WPT, several parameters that can be optimized to optimize power delivery are frequency, capacitor, and coupling coefficient (K). One of the obstacles encountered in WPT optimization precisely in the parameters of the coupling coefficient is the difficulty of knowing the exact value of the coefficient. This is because the coupling coefficient is a value between 0-1 that describes the degree of proximity between the sender and receiver coils. Therefore, an algorithm was designed to detect the coupling coefficient on WPT by comparing frequency responses using the Euclidean Distance method. This algorithm detects the coupling coefficient by calculating the distance between the input data and the dataset using the Euclidean Distance method. From the calculation of the distance, a dataset with the closest distance will be selected to take the value of the coupling coefficient as the output of this algorithm. The algorithm designed in this study managed to provide accuracy of 96.22% and an average computing time of 0.38 seconds.